Treatment of Semi-synthetic Metalworking Fluids: Membrane Filtration and Bioremediation - BUSCA, Gerald Thierry Michel (2004)
Waste engineering fluids, such as coolants and cutting fluids, are difficult to treat because they have variable physical natures, are particularly toxic and have a very high Chemical Oxygen Demand. The complex and unknown chemical content of the many different products available is also problematic. Current technologies, such as nanofiltration or chemical treatment, are quite effective at reducing the COD of the waste metalworking fluids before disposal. These technologies remove free or emulsified oil and high molecular weight components, but they have their limitations. In addition, the more stringent legislation on waste disposal and effluent discharge induces an economical stress on engineering industries. It can be anticipated that future legislations will introduce eco-toxicology measurements into industrial effluent discharge consents. A modular on-site treatment plant to treat semi-synthetic metalworking fluids was developed in this thesis. The approach was to combine different technologies and to inter-optimise their performances. The technologies used were membrane filtration, bioremediation and chemical treatment. The use of activated carbon was also studied. Membrane filtration included the study of ultrafiltration and nanofiltration. For the bioremediation process, a bio-consortia was developed and tested over 8 months. A final design of the whole process is given. The proposed treatment plant transforms the waste metalworking fluid into two products: very low chemical oxygen demand aqueous phase at 30 mg/l COD and a recovered oil showing a calorific value of 42 kJ/kg which could be a possible commodity. The whole treatment plant is scalled-up for thye treatment of 500 L of waste metalworking fluid per day.